The Effectiveness of Principal Leadership in Managing a Tahfidz- based Curriculum - Hairul Fauzi; Muh Ibnu Sholeh; Hawwin Muzakki; Muhammad Haris; Mohamed Ramadan Abd Allah Mohamed (Indonesian Research Journal in Education |IRJE|, 2024)
This study examines the role of principal leadership in managing the Tahfidz-based curriculum at MTs Hidayatul Hikmah Tanjung Jabung Barat, aiming to enhance students' character through intellectual and spiritual development via Quran memorization. This research employs a qualitative approach with a case study design, collecting data through interviews with the principal, teachers, students, and parents and direct observations of the implementation of the Tahfidz program. The data analysis technique is an interactive model, which includes data reduction, data presentation, and iterative conclusion drawing. The findings reveal that transformational leadership plays a crucial role in the effective implementation of the curriculum. The principal's clear vision, motivational strategies, and stakeholder engagement significantly contribute to the program's success. Key strategies, such as structured Tahfidz schedules, the Talaqqi method, and intensive mentoring, have improved students' Quranic memorization skills and comprehension. Despite its success, the program faces limited facilities, varying student motivation levels, and the need for enhanced teacher training.